2013
DOI: 10.1016/j.neures.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased mesiotemporal delta activity characterizes virtual navigation in humans

Abstract: Hippocampal theta or rhythmic slow activity (RSA) occurring during exploratory behaviors and rapid-eye-movement (REM) sleep is a characteristic and well-identifiable oscillatory rhythm in animals. In contrast, controversy surrounds the existence and electrophysiological correlates of this activity in humans. Some argue that the human hippocampal theta occurs in short and phasic bursts. On the contrary, our earlier studies provide evidence that REM-dependent mesiotemporal RSA is continuous like in animals but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 48 publications
(54 reference statements)
4
18
0
Order By: Relevance
“…This in turn could explain why oscillatory frequency may show an inverse relationship with brain size across species (Robinson, 1980, Herculano-Houzel, 2009). We note, though, that both non-invasive and semi-invasive recording approaches have also identified oscillations in the delta-theta band emanating from the MTL (de Araujo et al, 2002, Cornwell et al, 2008, Cornwell et al, 2012, Kaplan et al, 2012, Clemens et al, 2013). If greater number of phase cancelling sources alone is responsible for the difference in low-frequency oscillations between rats and primates, the presence of oscillations as far away as the scalp seems to weigh against this argument.…”
Section: Why Have Behavior-related Low-frequency Oscillations Been Elmentioning
confidence: 80%
See 1 more Smart Citation
“…This in turn could explain why oscillatory frequency may show an inverse relationship with brain size across species (Robinson, 1980, Herculano-Houzel, 2009). We note, though, that both non-invasive and semi-invasive recording approaches have also identified oscillations in the delta-theta band emanating from the MTL (de Araujo et al, 2002, Cornwell et al, 2008, Cornwell et al, 2012, Kaplan et al, 2012, Clemens et al, 2013). If greater number of phase cancelling sources alone is responsible for the difference in low-frequency oscillations between rats and primates, the presence of oscillations as far away as the scalp seems to weigh against this argument.…”
Section: Why Have Behavior-related Low-frequency Oscillations Been Elmentioning
confidence: 80%
“…Because MEG source localization to areas such as the MTL likely has an accuracy on the order of centimeters (Barnes et al, 2004), these methods cannot unambiguously pinpoint activity to specific sub-areas of the MTL. Human semi-invasive recordings that involve placing electrodes via entrance through the foramen ovale also suggest the presence of low-frequency movement-related oscillations emanating from the MTL during VR navigation (Clemens et al, 2013). A non-human primate study also demonstrated theta oscillations and spike/phase coupling in the MTL (entorhinal cortex) when monkeys looked at objects (Killian et al, 2012), which the authors related to movement-related changes.…”
Section: Hippocampal Low-frequency Oscillations In Primatesmentioning
confidence: 99%
“…B 369: 20130304 behaviours (figure 3b). Oscillations at 1-4 Hz most often increased in amplitude during periods of virtual movement compared with stillness ( [54], see also [57]). Follow-up work showed that, such as theta in rodents [30], the amplitude of these 1-4 Hz oscillations positively correlated with the speed of movement [55].…”
Section: Hippocampal Theta Oscillations In Humansmentioning
confidence: 99%
“…Indeed, growing evidence indicates that slow theta activity (peaking at 3 Hz) in the human hippocampus may be the functional equivalent to the hippocampal theta rhythm of rodents (Jacobs, 2014;Watrous et al, 2013). For example, when previous findings in rats (Vanderwolf, 1969) were replicated in neurosurgical patients with depth recordings in hip pocampus, it was observed that activity in slower frequencies (1 4 Hz) increased with movement in virtual navigation (Clemens et al, 2013;Ekstrom et al, 2005;Watrous et al, 2011). In addition, MEG studies have shown that better navigation performance is related to increased hippocampal activity at slow theta frequencies (Cornwell et al, 2008;Kaplan et al, 2012).…”
Section: Introductionmentioning
confidence: 98%